Cloning and expression of \( pigI\) gene in \(Escherichia coli\) BL21 (DE3) - Minh Trung, Do; Hai Quynh, Do; Thuy Duong, Nguyen (Academia Journal of Biology, 2021)
Prodigiosin (Pg), a secondary metabolite with anticancer and antimicrobial activities, can be produced in Serratia marcescens bacteria through the condensation reaction of 4-methoxy-2, 2’-bipyrrole-5-carboxyaldehyde (MBC) and 2-methyl-3-amylpyrrole (MAP). Among these, the MBC synthetic pathway is started by the conversion of L-proline to L-proline-AMP before this complex is covalently attached to PigG. This reaction is catalyzed by an L-prolyl-AMP ligase named PigI. Therefore, PigI protein plays an important role in the prodigiosin biosynthetic pathway. However, studies related to PigI protein have not been carried out in Vietnam yet. In this work, the pigI gene was cloned and expressed in Escherichia coli DH10B and BL21 (DE3), respectively. Sequence alignment results revealed that the obtained pigI gene is 99.7% identical to the four strains, CP027798, CP027796, CP021984 and CP003959. This recombinant vector pJET1.2/pigI was used to reamplify pigI, and the acquired amplicon was inserted into pET22b vector at the site of HindIII and XhoI. The clone E. coli BL21 (DE3) containing the recombinant vector pET22b/pigI was expressed in an auto-induced medium. The presence of PigI protein in the lysate was identified due to a 53 kDa band through Western Blot analysis using an anti-his-tag antibody. The results of our study provide a potential method for producing prodigiosin from recombinant protein in Vietnam.